DNA Detection Sensitivity Test from Blood Sample Extraction of Sumatran Elephant (Elephas Maximus Sumatranus) Male at Elephant Training Center, Way Kambas National Park Using Simple and Molecular Methods - Neli Pratiwi, Dian; Priyambodo, Priyambodo; Angeliya, Liza; Agus Srihanto, Eko; Candra, Dedi; Devi Krismuniarti, Elisabeth; Lestari Rustitati, Elly (Jurnal Agrosci, 2023)
DNA detection of male sumatran elephants' (Elephas maximus sumatranus) blood samples using simple and molecular methods are ways to find out the DNA quality from extracted samples. Molecular biology analysis was done in Biotechnology Laboratory, Lampung Disease Investigation Center, under the Institution Nation Strategy Grant, Directorate General of Research Empowerment and Development, Ministri of Research, Technology and Higher Education 2018 Number 393/UN26.21/PN/2018. Sensitivity test on 12 blood samples was conducted using simple and molecular methods. Simple method is based on 1% gel agarose electrophoresis in TAE (Tris-acetate EDTA) buffer while molecular method involves Polymerase Chain Reaction (PCR) based Glyseraldehyde-3-Phosphate Dehydrogenase (GAPDH) primer. Of 12 samples extracted and tested, 10 samples using molecular method showed DNA bands. Sensitivity value (83.33%) of diagnostic calculation showed that molecular method is more sensitive in detecting DNA.